The Effect of Different Temperature and Methanol Concentration on Current Density Distribution of Direct Methanol Fuel Cell - Nurul Syazwani Bte Abd. Jabar, Nurul Syazwani (Universiti Teknologi Petronas, 2012)
The effect of different temperature and methanol concentration on current density distribution of DMFC is presented in this paper. DMFC are a subcategory of proton exchange membrane fuel cells (PEMFC) in which methanol is used as the fuel. The performance of direct methanol fuel cell must be evaluated with different possible operating condition for being commercialize especially in the area of small scale portable power production. 2D model is more computational efficient compared to 3D and more accurate than 1D. Hence, two-dimensional model, x-y plane geometry is utilized in the simulation to take into account the transport phenomena in all layers in the cell. The simulation was done based on agglomerate model of PMFC in COMSOL Multiphysics 3.5a. Theory and governing equations involve are Maxwell-Stefan, Darcy’s Law, agglomerate model of anode and cathode and porous fluid flow. Different operating parameter which are temperature ranging from 323K to 353K and methanol concentration ranging from 2M to 5M based on literature survey were employed. Finally, the model were analyze with postprocessing tools in COMSOL to get required plot. The result can be concluded that current density distribution increases with increasing temperature and concentration. Future study can be done by assuming membrane to be permeable to the reactant.